MOTIVASI KADER POSYANDU DALAM PEMERIKSAAN IVA TEST - Sarumpaet, Erni Yanti; Lela Hartini, Sri Sumiati AB, (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
Inspection of Visual Inspection of Acetic Acid (IVA) is one way of earlydetection of cervical cancer disease. This check method is an easy-to-do and inexpensivemethod, but has high yield accuracy. The Srikuncorocommunity Health centersiscommunity Health centers which has the lowest IVA examination rate that is 5 people.The purpose of this research is to know factors related to posyandu cadre motivation inexamination of IVA test in working area of The Srikuncorocommunity Healthcenters2017 This research use cross sectional method. The population of the research wasposyandu cadres in The Srikuncorocommunity Health centersarea of 90 people, with totalsample technique. Using secondary data and primary data with univariate, bivariate, andmultivariate analyzes. The research results of most cadres received poor husband support(56.7%), poor environmental support (54.4%), poor information exposure (55.6%), andmost cadres have low motivation (62.2%). There is a significant relationship betweenhusband support p = 0,000 and OR = 10,750, environmental support p = 0,000 and OR =8,883, information exposure p = 0,000 and OR = 7,593 with cadre motivation in IVA testexamination at Puskesmas Srikuncoro 2017. husband is the most influential factor withcadre motivation in IVA examination